Effectiveness of Mediation as an Alternative for International Business Dispute Resolution - Adiasih, Ning (JURNAL AKTA, 2025)
Mediation as an alternative dispute resolution is considered to have beneficial power. Mediation can produce a win-win solution for the parties. Mediation is a relatively inexpensive and time-consuming segregative dispute resolution process; dispute resolution through mediation efforts has also been known in the culture of Indigenous peoples in Indonesia for a long time. This study aims to describe and analyze the effectiveness of Mediation as an alternative to resolving business disputes outside the court. This study was conducted using a literature study method. The study results indicate that using Mediation as an alternative to resolving disputes outside the court is effective because, in implementing non-litigation Mediation, both parties are examined in private (not open to the public). That way, the positive impact on the credibility and reputation of the disputing parties is maintained. In addition, compared to the litigation process, out-of-court Mediation is cheaper, less complicated, and does not take long. On the other hand, out-of-court Mediation pays close attention to the continuity of the future relationship between the parties. This is why businesses prefer out-of-court Mediation as an alternative to resolving their business disputes.